ASSESSMENT OF THE EFFECTIVENESS OF DARLING AND BIZZIBODI RADIO STATIONS IN CREATING AWARENESS AGAINST DRUG ABUSE IN OWERRI MUNICIPAL - Orekyeh, Emeka S. S; Tonga, Ahmed Abdullahi; Okeke, Somtochukwu Victor; Igbokwe, Ugochi Rita (African Journal of Social and Behavioural Sciences, 2023)
The study examined the effectiveness of Bizzibodi and Darling radio stations in creating awareness against drug abuse in Owerri Municipal. The study made use of the agenda-setting and uses and gratifications theories. A sample size of 384 was adopted. The survey research method was used for this study and questionnaire was used for data collection. The study raised three research questions to help guide the study. The study revealed that respondents to a high level listen to drug abuse messages on Bizzibodi and Darling radio stations. The study also revealed that the respondents hold a positive perception towards the drug abuse messages aired on the radio stations. The study recommended that government and opinion leaders should keep broadcasting more messages on radio as a majority of the respondents in Owerri municipal LGA have and listen to the radio. Furthermore, broadcasters should present drug abuse messages in native tongues of their target audience so as to increase awareness, interest and garner more audience. Finally, drug law enforcement bodies such as National Drug Law Enforcement Agency (NDLEA) should frequently create awareness messages on radio.